Analysis of Measured Data in Unbalanced Distribution System and Method of Making of Distribution System Model for Analyzing. Issue 1 (April 2017) - FUJITA, YU; KOBAYASHI, HIROSHI; KODERA, TAKANORI; AOKI, MUTSUMI; SUZUKI, HIROTO; ISHIKAWA, HIROYUKI; MIWA, TAKURO
SUMMARY: In recent years, rapid introduction of photovoltaic power systems (PVs) causes voltage rise in distribution systems. In addition, residential PVs cause voltage unbalance in distribution systems. For these reasons, it has become difficult to control voltage in distribution systems to within the allowable range. Therefore, it is necessary to consider the voltage unbalance suppression method corresponding to the measured data in unbalanced distribution systems. Thus, we measured voltage on the distribution lines that are expected to large voltage imbalance and analyzed the reality of voltage unbalance. Also, static VAR compensator is suitable for voltage unbalance suppression, although it is expensive. Therefore, we make the distribution system model using the measured voltage in distribution systems to verify the voltage unbalance suppression effect.